ANALYSIS OF GATED SPACE IN SURABAYA CITY ON THE SOCIAL RESILIENCE OF THE CITY - Emillio , Sebastianus; Damayanti , Rully (ADBE, 2025)
According to Henri Lefebvre's third space theory, "contested space" refers to the struggle for and defense of space. This study, carried out in Surabaya, looks at the causes of third spaces' formation. While some people informally settle in the observed location, resulting in locals barricading their homes. Because of their separation, these disparate traits create barriers that erode social ties. The study uses qualitative methods to gather data on the contested space phenomenon, such as literature reviews and field surveys. Results describe the processes that give rise to contentious places. Based on observations, homeowners build barriers to provide security from strangers or undesired infiltration due to differences in socioeconomic position, which erodes social interactions. According to this study, social segregation in contentious public spaces might reduce a city's social resilience. As a result, social contacts among individuals become less meaningful, which has an effect on Surabaya resilience. The study concludes that contested spaces in public places impair social resilience, which affects Surabaya by causing social segregation and a decline in the quality of social interactions. The goal of the project is to improve knowledge of this phenomenon and increase awareness of how crucial social interaction is to the social resilience of cities.